Optimisation of energetic and reproductive gains explains behavioural responses to environmental variation across seasons and years. (18th March 2020) - Studd, E. K.; Menzies, A. K.; Siracusa, E. R.; Dantzer, B.; Lane, J. E.; McAdam, A. G.; Boutin, S.; Humphries, M. M.
Abstract: Animals switch between inactive and active states, simultaneously impacting their energy intake, energy expenditure and predation risk, and collectively defining how they engage with environmental variation and trophic interactions. We assess daily activity responses to long‐term variation in temperature, resources and mating opportunities to examine whether individuals choose to be active or inactive according to an optimisation of the relative energetic and reproductive gains each state offers. We show that this simplified behavioural decision approach predicts most activity variation ( R 2  = 0.83) expressed by free‐ranging red squirrels over 4 years, as quantified through accelerometer recordings (489 deployments; 5066 squirrel‐days). Recognising activity as a determinant of energetic status, the predictability of activity variation aggregated at a daily scale, and the clear signal that behaviour is environmentally forced through optimisation of gain, provides an integrated approach to examine behavioural variation as an intermediary between environmental variation and energetic, life‐history and ecological outcomes. Abstract : By assessing daily activity responses to long‐term variation in temperature, resources, and mating opportunities, we examine whether individuals choose to be active or inactive according to an optimization of energetic and reproductive gains. This simplified behavioural decision approach predicts most daily activity variation ( R 2  = 0.83) expressed by free‐ranging red squirrels over four years, as quantified through accelerometer recordings. Here we provide an integrated approach to examine behavioural variation as an intermediary between environmental variation and energetic, life‐history, and ecological outcomes.